Numerical Simulation on the Dynamic Variation of Reservoir Pressure of Typical Coalbed Methane Single Well and Well Net Group—A Case Study on QN01 Well in the Southern Qinshui Basin, China. Issue 2 (March 2013) - Zou, Mingjun; Wei, Chongtao; Li, Laicheng; Yang, Yongguo; Lei, Bo
Based on the geological data and drainage parameters of QN01 coalbed methane (CBM) well which is located at the southern Qinshui Basin, by using CBM reservoir numerical modeling technology, 15 years' gas recoverability is predicted and the dynamic variation of reservoir pressure is studied for both QN01 well and an assumed 300 × 300m well net group by using the same parameters as QN01 well. The results show that for single well, within the first 300 days, gas recoverability is similar everywhere in the gas supply area and the dropping rates of reservoir pressure are all below 1 KPa/d. Further more, the region more than 120 m away from the well bore hole is not beneficial for gas recoverability. For well net group, dropping rates of reservoir pressure are higher than 1 KPa/d. With the increase of the distance to the well bore hole, gas outcomes more and more in the gas supply area. Similarly, the "secondary reservoir pressure dropping" caused by the well interference in the well net group has a positive correlation with the distance to the well bore hole, and the dropping rates of reservoir pressure of the well net group are approximately twice as large as those of the single well.